Dynamic Evaluation of the Merdeka Curriculum: Unveiling the Effectiveness of Science Lesson Planning, Implementation and the Response of Junior High School Students - Henukh, Anderias; Riandi, Riandi; Setiawan*, Agus; Rochintaniawati, Diana; Irvani, Asep Irvan; Suba, Joey M (Jurnal Pendidikan Sains Indonesia, 2024)
Merdeka curriculum is an education initiative in Indonesia that gives educators the flexibility to create learning that is more in-depth and suited to the needs of learners. This curriculum focuses on strengthening character and developing essential competencies, allowing students to go deeper into concepts and develop skills that are relevant to the challenges of the times. However, there are many obstacles in its implementation, especially in science learning, so it needs to be analyzed more deeply. The purpose of the research is to describe the planning, implementation, assessment, and students' responses to the implementation of the Merdeka curriculum in junior high school science subjects. The method used in this research is descriptive-quantitative. The subjects of this study were junior high school science teachers and students in grade VII in one of the private schools in the city of Bandung. The instruments used in this study were observation sheets and questionnaires. Based on the data analysis above, it can be concluded that the average score of science learning planning in the independent curriculum is 3.15, so it is in the good enough category. The average score of the science learning assessment obtained is 2.5, so it can be said that teachers still do not carry out learning assessments well. The average for all aspects of learner response has a good category, namely 73.62%. Thus, it is suggested that the teacher prepare everything related to learning activities to the maximum so that maximum results can be obtained